PENDAFTARAN TANAH SECARA ELEKTRONIK DI KANTOR PERTANAHAN KOTA PADANG - Marjoni, Salma; Hasbi, Muhammad; Rosari, Anton (Penerbit Lafadz Jaya, 2025)
This study discusses the implementation of electronic land registration at the Padang City Land Office, which is part of the digital transformation agenda for public services in the land sector. The main problem in this study is formulated in two questions: (1) How is the implementation of electronic land registration at the Padang City Land Office? and (2) How are efforts to overcome obstacles in the implementation of electronic land registration at the Padang City Land Office. This study uses an empirical juridical approach, namely a method that examines law as real behavior in society. Data were obtained through a literature study of laws and regulations, official documents, and interviews with Land Office employees, PPAT, and the community. This study uses the theory of legal certainty and the theory of legal protection as an analytical framework. The results of the study show that the implementation of electronic land registration at the Padang City Land Office is still in the early stages of implementation and has not run optimally. Although regulated by the Minister of ATR/BPN Regulation Number 3 of 2023, as of January 2025, the conversion rate from analog certificates to electronic certificates had only reached approximately 1.53% of the total land parcels in Padang City. Several major obstacles identified included inconsistencies between physical and electronic data, technical system disruptions, low digital literacy among the public, and incomplete outreach efforts involving the Padang City Land Office and the community.